Presidential Decree-Law No. 106 of The Year 2013 On The Prohibition Of Conflict Of Interests Of Public Officials = قرار رئيس جمهورية مصر العربية بالقانون رقم 106 لسنة 2013 فى شأن حظر تعارض مصالح المسئولين فى الدولة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.